Are Cross-Sectional Imaging Modalities Enough for Sarcopenia Assessment? - Haluk Tarık Kani; Elif Tufan (Turkish Journal of Gastroenterology, 2024)
Cite this article as: Kani HT, Tufan E. Are cross-sectional imaging modalities enough for sarcopenia assessment? Turk J Gastroenterol. 2024;35(1):73-74.